ITIL 2011: Maturity Level of Service Operation - Rekha Bella Novia; Wella . (IJNMT (International Journal of New Media Technology), 2019)
Service quality is a measurement from users’ hope to the company in fulfilling their needs and desires also service delivery accuracy. Technology and information services can help the company in supporting the company’s business operations. Therefore, the company needs to apply ITSM (Information Technology Service Management) as an operational approach of technology and information services to keep the service quality in the company. The framework that is focusing on providing technology and information services which can be used as a guide is the ITIL framework (Information Technology Infrastructure Library). This research is conducted at PT Pertamina (Persero). The research is conducted using the 2011 ITIL framework on Domain Service Operation with 5 processes in it which are Incident Management, Request Fulfillment, Event Management, Access Management, and Problem Management. The methods that are used in this research are interview and questionnaires. This research is conducted based on research steps by Gallegos 2008, which consist of 5 steps such as the planning, the field checking, the report, and the follow-up. Based on the research conducted there are three processes that are stopped at level 1 which is Incident Management with score 62.54%, Problem Management with score 79.08% and Request Fulfillment with score 81.09%. Meanwhile, on the Access Management process achieve 86.00% and Access Management is stopped at level 2 with score 77,23%.